Spermidine triggering effect to the signal transduction through the AtoS–AtoC/Az two-component system in Escherichia coli - Theodorou, Marina C.; Theodorou, Evaggelos C.; Panagiotidis, Christos A.; Kyriakidis, Dimitrios A. (Biochimica et biophysica acta, 2007)
Recent analysis revealed that, in Escherichia coli the AtoS–AtoC/Az two-component system (TCS) and its target atoDAEB operon regulate the biosynthesis of short-chain poly-( R)-3-hydroxybutyrate (cPHB) biosynthesis, a biopolymer with many physiological roles, upon acetoacetate-mediated induction. We report here that spermidine further enhanced this effect, in E. coli that overproduces both components of the AtoS–AtoC/Az TCS, without altering their protein levels. However, bacteria that overproduce either AtoS or AtoC did not display this phenotype. The extrachromosomal introduction of AtoS–AtoC/Az in an E. coli Δ atoSC strain restored cPHB biosynthesis to the level of the atoSC + cells, in the presence of the polyamine. Lack of enhanced cPHB production was observed in cells overproducing the TCS that did not have the atoDAEB operon. Spermidine attained the cPHB enhancement through the AtoC/Az response regulator phosphorylation, since atoC phosphorylation site mutants, which overproduce AtoS, accumulated less amounts of cPHB, compared to their wild-type counterparts. Exogenous addition of N 8-acetyl-spermidine resulted in elevated amounts of cPHB but at lower levels than those attained upon spermidine addition. Furthermore, AtoS–AtoC/Az altered the intracellular distribution of cPHB according to the inducer recognized by the TCS. Overall, AtoS–AtoC/Az TCS was induced by spermidine to regulate both the biosynthesis and the intracellular distribution of cPHB in E. coli.